Gypenosides regulate autophagy through Sirt1 pathway and the anti-inflammatory mechanism of mitochondrial autophagy in systemic lupus erythematosus. Issue 5 (2nd May 2022) - Ke, Jin-Yong; Liu, Zhi-Yong; Wang, Yun-Han; Chen, Shi-Ming; Lin, Jing; Hu, Fang; Wang, Yu-Fang
ABSTRACT: To study the mechanism of gynostemma pentaphyllum saponins (GpS) regulating mitochondrial autophagy and anti-inflammatory through Sirtuin 1 (Sirt1) pathway in systemic lupus erythematosus (SLE). JURKAT cells were cultured in vitro, RT-PCR and western blotting (WB) were utilized to identify the expression of related-proteins in Sirt1 pathway and global autophagy and mitochondrial autophagy markers in JURKAT before and after GpS treatment induced by ultraviolet B (UVB), and the related-mechanism of GpS regulation of autophagy was analyzed. The SLE model was established to analyze the alleviating effects of GpS on various symptoms of lupus mice. Sirt1/AMPK/mTOR pathway was activated in UVB induced JURKAT cells. After the addition of GpS, WB revealed that the phosphorylation of AMPK decreased, the phosphorylation of mTOR increased, the expression of Sirt1 protein decreased, and the activation of the pathway was inhibited. Moreover, autophagy of JURKAT cells wasinhibited. In order to further verify the role of Sirt1 pathway, we activated Sirt1 expression in cells by constructing lentiviral vectors, and the therapeutic effect of GpS was significantly reduced. These results indicate GpS can exert autophagy regulation by inhibiting the activity of Sirt1 pathway. To treat SLE. GpS can significantly reduce the level of autoantibodies, kidney inflammation, immune complex deposition and urinary protein excretion, improve kidney function in lupus-prone mice. GpS can regulate autophagy and mitochondrial autophagy through Sirt1 pathway, which may be a potential mechanism for GpS to reduce the level of autoantibodies, kidney inflammation, immune complex deposition and urinary protein excretion, improve kidney function in lupus-prone mice. Graphical abstract: uf0001